2005
DOI: 10.1097/01.wnr.0000185960.11465.16
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of adeno-associated virus type-2 vectors in non-human primate Schwann cells

Abstract: Adult macaque Schwann cells were infected using adeno-associated virus type-2-derived vectors expressing the green fluorescent protein reporter gene under the control of the cytomegalovirus, the hybrid cytomegalovirus-betaactin, the myelin basic protein or the tetracycline-inducible promoters. On the basis of green fluorescent protein expression, gene transfer efficiency was compared in resting and dividing conditions following or not following hydroxyurea or etoposide treatment. Hydroxyurea allowed promoter-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While mammalian viral vectors derived from retroviruses, lentiviruses, adenovirus or adeno‐associated virus (Girard et al. 2005; Watanabe et al.…”
Section: Discussionmentioning
confidence: 99%
“…While mammalian viral vectors derived from retroviruses, lentiviruses, adenovirus or adeno‐associated virus (Girard et al. 2005; Watanabe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Adeno-associated viral vectors are increasingly regarded as safe and are well-tolerated following application to the human brain. AAV2 and 8 transduce primate and rat Schwann cells ( Girard et al, 2005 ; Homs et al, 2011 ). As a first step toward optimizing AAV-mediated gene transfer to Schwann cells we performed a screen of all 9 common serotypes and showed that AAV2 vectors outperform other serotypes in transducing Schwann cells in human peripheral nerve explants, whereas several AAV serotypes efficiently transduced rat Schwann cells ( Hoyng et al, 2015 ).…”
Section: Perspective On Future Steps To Accomplish Recovery Of Functimentioning
confidence: 99%